Digitalization of Human Head Anthropometry Measurement Using Pixels Measurement Method - Fandy Surya Pratama; Istianah Muslim; Muhammad Ihsan Zul (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
Head Anthropometry is a part of anthropometry that needed to be measured carefully. It is because human head becomes an important part that necessary to be protected. The protection aims to look after the safety of the human head. Safety factors can be achieved by designing head products. Therefore, head anthropometry data is required to make a product design Currently, data retrieval of head anthropometry is still using several measuring devices such as anthropometers, sliding callipers, spreading callipers, and tape gauges. This measurement method makes the standard deviation become higher and also take a lot of time to capture huge amounts of anthropometry data. However, the problem has been resolved by other study research with building a head dimension measurement system using digital camera. But the system still need the integration with digital camera. This study uses the IP Camera that has been integrated with the system to capture human head from the front and side. The captured image is segmented into several areas based on head dimension. Then, the image is processed using pixel measurement method by performing feature extraction on each head dimension to get the result of head dimension measurement. The result shows that calliper measurement and system measurement against ten of fourteen human head anthropometry dimensions is identical with the best distance between IP Camera and the head as far as 200 cm. This head anthropometry data is expected to make a contribution to Indonesian Ergonomics Society.